[Curpite dancers taking a meal break] - Esmerelda Landin::::::photographer::: (2005)
Description supplied by photographer: 'Aquí se aprecia donde alimentan a algunos de los Curpites. Cada día de la celebración, la comunidad se une para proveerlos con desayuno, almuerzo y cena. Este sitio es la casa de mis primas Lorena y Connie, en el barrio de San Mateo.' - 'These are some of the Curpite dancers that are being provided with food. Every day of the dance competitions the community pitches in to make breakfast, lunch and dinner for all of the participants. This location is at the house of my cousins Lorena and Connie, which is located in Barrio San Mateo.'